2019
DOI: 10.37358/rc.18.12.6836
|View full text |Cite
|
Sign up to set email alerts
|

Novel Formulation Based on Chitosan-Arabic Gum Nanoparticles Entrapping Propolis Extract Production, physico-chemical and structural characterization

Abstract: The aim of our study was to prepare and characterize chitosan-based nanoparticles encapsulating propolis extract by ionotropic gelation and glutaraldehyde cross-linking technique. Both spectroscopic (UV-Vis, FTIR) and microscopic techniques (AFM) were applied for structural characterization of nanoparticles, along with entrapment and release study of propolis extract. The physico-chemical properties and morphological features of the obtained nanoparticles demonstrated a good correlation between all the investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…The images revealed the spherical shape of nanoparticles, and their diameter ranging from 100 to 200 nm, in concordance with the DLS results. By comparing these results with our previously reported ones [8], a smaller diameter and regular shape can be noticed, demonstrating that the above preparation method is more adequate for pharmaceutical applications. The present results are also supported by other researches in this field, which demonstrated that the production of nanoparticles by ionic gelation results in smaller particles for higher amounts of cross-linker, providing sufficient protonation of chitosan for interaction with TPP [39][40].…”
Section: Morphological Characterization Of Chitosan/propolis Nanopartsupporting
confidence: 78%
See 2 more Smart Citations
“…The images revealed the spherical shape of nanoparticles, and their diameter ranging from 100 to 200 nm, in concordance with the DLS results. By comparing these results with our previously reported ones [8], a smaller diameter and regular shape can be noticed, demonstrating that the above preparation method is more adequate for pharmaceutical applications. The present results are also supported by other researches in this field, which demonstrated that the production of nanoparticles by ionic gelation results in smaller particles for higher amounts of cross-linker, providing sufficient protonation of chitosan for interaction with TPP [39][40].…”
Section: Morphological Characterization Of Chitosan/propolis Nanopartsupporting
confidence: 78%
“…As the administration of phenolic compounds requires a special formulation with protecting systems, able to maintain the structural integrity of the bioactive compounds until the moment of consumption, micro and nano-encapsulation techniques have emerged as a prominent solution to the bioavailability of the therapeutic agent [8]. Chitosan is one of the most suitable and affordable natural polymers used as a *email: florinbanica1@gmail.com; dobjanschil@yahoo.com # Authors with equal contribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen type I from bovine Achilles tendon and chitosan (medium molecular weight, deacetylation degree >75%), were purchased from Sigma-Aldrich. Preparation of chitosan nanoparticles entrapping propolis extract was reported in our previous work [18], using an eco-friendly method. Briefly, a mixture of propolis extract and Arabic gum was added gradually, by vigorous stirring, to chitosan solution, and then, glutaraldehyde cross-linking agent was injected by syringe, under continuous stirring, allowing nanoparticles formation.…”
Section: Production Of Collagen Films With Chitosan/propolis Nanoparticles Incorporatedmentioning
confidence: 99%
“…As presented in literature, the administration of phenolic and flavonoid compounds requires special formulation, with the aim to protect and maintain the structural integrity of the compounds, concomitant with the increase of its water solubility and bioavailability [16]. Micro and nano encapsulation techniques are available, using polymers of natural or synthetic origin, or lipids [17,18] the resulted products being widely used in the food technology, pharmaceutical and cosmetic industries, biomedical and sensor industries. In the light of recent developments in the wound management field, the aim of our work was to prepare and to investigate the structural, morphological and antibacterial properties of novel collagen film with chitosan nanoparticles entrapping propolis extract, as an advanced and eco-friendly wound dressing device.…”
mentioning
confidence: 99%